Assessing the Impact of Educational Status on Poverty Alleviation in Khyber Paktunkhwa, Pakistan - Aurangzeb Khan, Muhammad; Zari Rafiq, S. (The Journal of Humanities & Social Sciences, 2023)
The core purpose of this study was to assess the impact of educational status on poverty alleviation in Khyber Pakhtunkhwa. The major hypothesis developed for this study was that higher literacy rate among people had greater potentials to combat poverty. The nature of the respondents was male both literate and illiterate falling in the age group of (18-60) years and above from the slum areas of four randomly selected districts of Khyber Pakhtunkhwa namely Mardan, Kohat, Haripur and Chitral respectively. A sample size of 800 respondents was drawn out from the target population. Interview schedule, designed on Likert Scale was used as tool and interview as method for data collection. Chi-square test was used to measure the association between two variables i.e. dependent variable (Poverty Alleviation) and independent variable (Educational Status). A relationship was measured among occupation (P = 0.000), monthly income (P = 0.000), per capita income of the educated respondents (P = 0.000), per capita income of the illiterate respondents (P = 0.000), house condition(P = 0.000), possession of property(P = 0.000), type of property (P = 0.000), size of land(P = 0.000), affordability of medicines (P = 0.000), specialist doctor and hospitalization (P = 0.000) with educational status. Free education, investment in education and improvement of existing formal education system were forwarded as recommendations in light of the study.